2010
DOI: 10.1021/ma101115t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Narrowly Size-Distributed Thermosensitive Poly(N-isopropylacrylamide) Nanocapsules in Inverse Miniemulsion

Abstract: Narrowly size-distributed thermosensitive poly(N-isopropylacrylamide) (PNIPAM) nanocapsules with a hydrophilic core composed of an aqueous solution of cobalt tetrafluoroborate (CoTFB) were synthesized via a one-pot polymerization of N-isopropylacrylamide (NIPAM) and the cross-linking agent N,N′-methylene bis(acrylamide) (MBA) in inverse miniemulsion. CoTFB not only worked as template and lipophobe, but also promoted the dissolution of NIPAM in water by the formation of a complex between NIPAM and CoTFB. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 38 publications
4
45
0
1
Order By: Relevance
“…[3,12] Whereas sub-micrometer-scale capsules are attractive for delivery and controlled release applications that rely on cellular uptake, [13] larger microgel capsules are attractive for the opposite purpose of encapsulation of cells within the microgel. [9] Established experimental techniques to fabricate sub-micrometer-scale microgel capsules include precipitation polymerization, [14][15][16][17][18][19] emulsion and miniemulsion templating, [20][21][22][23][24] and template-supported layerby-layer assembly [25][26][27][28][29][30][31][32][33] as well as grafting. [34][35][36][37] The fabrication of larger microgel capsules, however, is challenging.…”
Section: Microgels: Soft Small Superbmentioning
confidence: 99%
“…[3,12] Whereas sub-micrometer-scale capsules are attractive for delivery and controlled release applications that rely on cellular uptake, [13] larger microgel capsules are attractive for the opposite purpose of encapsulation of cells within the microgel. [9] Established experimental techniques to fabricate sub-micrometer-scale microgel capsules include precipitation polymerization, [14][15][16][17][18][19] emulsion and miniemulsion templating, [20][21][22][23][24] and template-supported layerby-layer assembly [25][26][27][28][29][30][31][32][33] as well as grafting. [34][35][36][37] The fabrication of larger microgel capsules, however, is challenging.…”
Section: Microgels: Soft Small Superbmentioning
confidence: 99%
“…Emulsion II PRBO and Emulsion II BRBO had significantly ( p < .05) lower droplet sizes compared to Emulsion I PRBO or Emulsion I BRBO, which indicated that the 10 min of shearing effectively decreased the emulsion droplet sizes. The polydispersity index (PdI) is a dimensionless number that describes the heterogeneity of the sample, and it can range from 0 (monodisperse) to 1 (very polydisperse) (Cao, Ziener, & Landfester, ). Emulsion II PRBO and Emulsion II BRBO exhibited more monodisperse characteristics (Figure ) than Emulsion I PRBO and Emulsion I BRBO.…”
Section: Resultsmentioning
confidence: 99%
“…Several groups further developed this approach by introducing crosslinker in the miniemulsion systems to endow the PNCs with crosslinked structures . In addition to normal oil‐in‐water miniemulsions, inverse water‐in‐oil miniemulsion have also been used for the preparation of CPNCs using this approach …”
Section: Emulsion Interfacial Crosslinkingmentioning
confidence: 99%